Erasing borders at Teltow Canal Berlin - Jacobsson, Johan; Soldemo, Svante (2016)
The thesis investigates alternatives to contemporary urban planning. The aim is to find solutions to how a more flexible development can be brought about in the specific area around the Teltow Canal on the outskirts of Berlin. In the thesis, it argues that planning regulations and methods have not been able to keep up with the rapid changes in society which has led to urban environments not being flexible enough when conditions change. To find methods and ideas for solutions, a literature study of contemporary sources on the subject was conducted. The literature study is presented in a theoretical framework divided into the three themes; Flexible Urban Planning, Small-scale Interventions and Interim Use. From the conclusions drawn from the themes, a number of design concepts are established and presented in a conceptual framework. The concepts include reusing and retaining elements of the area, multifunctional material and design, open planning process, accessibility to and adaptability of areas, and establishing clear frameworks for future development. The study of the district chosen for the thesis shows that it contains extensive green spaces along the Teltow Canal as well as built environment of historical and cultural importance. The area also exhibits a lack of infrastructure and accessibility. The proposal is based on the examples and methods studied in literature. The idea combines the strength of the existing green spaces with the implementation of a new green path network. It will act as a framework for future urban development and at the same time ensure a connectivity of green spaces over time. Within the green path network a series of interventions are proposed. By adapting to the existing conditions and reusing and retaining physical characteristics, the interventions open up spaces for new connections, uses and possibilities. All interventions are placed at strategic points in the area to have a catalytic effect, guiding the future development of the surrounding environment.